Tugas & Fungsi Bbksda-Gakkum Klhk Dalam Proses Penanganan Tindak Pidana Perdagangan Satwa Yang Dilindungi Jenis Biawak Timor (Varanus Timorensis) & Ular Malkoti (Liasis Mackloti) Di Wilayah Nusa Tenggara Timur - Tadon, Agustine Cindy; Leo, Rudepel Petrus; Wilhelmus, Bhisa Vitus (Artemis Law Journal, 2025)
The problem to be studied in this research is the process of handling criminal acts of trade in protected wildlife species, namely the Timor Monitor Lizard (Varanus Timorensis) and the Malkoti Snake (Liasis Mackloti) in the East Nusa Tenggara region. The role of the Institute for Conservation of Natural Resources and Ecosystems and the Environmental & Forestry Law Enforcement and Security Center is to ensure the protection and management of natural resources and ecosystems, in the process of law enforcement against protected wildlife trade is as a place to deposit evidence, namely wildlife that has been secured from the hands of the perpetrators. This study is an empirical juridical research, utilizing both primary and secondary data sources. Primary data was gathered through interviews with relevant sources, while secondary data was collected by visiting locations to obtain the required information. Data were analyzed descriptively-qualitatively. The duties & functions of BKSDA Gakkum-KLHK in the handling process are in accordance with the provisions of Article 21 paragraph (2) of the Law on Conservation of Living Natural Resources & Ecosystems and Article 40 of Law No. 5 of 1990. Factors causing the occurrence of animal trafficking crime are caused by two factors, namely internal factors and external factors.